Analysis of single pole reclosing on EHV line in Thailand - K. Ngamsanroaj (2018)
This paper presents an investigation of single pole reclosing on EHV transmission lines in Thailand. The reactor compensation of single pole switching on both single and double circuit lines is reviewed. The existing EHV line is simulated. At the boundary of the simulation, the external grid was represented by positive/zero sequence equivalent impedances. All simulations were done with EMTP. Methods of reducing this secondary current are considered in this paper. © 2007 IEEE.